Continuous and Comprehensive Evaluation in School Education: A Critical Qualitative Review of Its Conceptual Framework, Implementation Practices, and Challenges. - Dr. Aadil Hussain Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Continuous and Comprehensive Evaluation (CCE) represents a major reform in educational assessment, aiming to shift from traditional examination-oriented practices to a more holistic and continuous evaluation of students’ overall development. This qualitative review paper critically examines the conceptual foundations, implementation practices, advantages, and challenges associated with CCE in school education. Drawing upon policy documents, theoretical perspectives, and existing empirical studies, the paper highlights that CCE promotes formative assessment, encourages regular learning, reduces examination-related stress, and enhances student engagement and participation in the learning process. It also supports the assessment of both scholastic and co-scholastic domains, thereby fostering holistic development. However, despite its progressive intent, the implementation of CCE has faced several challenges, including inadequate teacher training, increased administrative workload, lack of clarity in evaluation procedures, and limited infrastructural support in schools. These constraints have affected the consistency and effectiveness of its application across different educational contexts. The paper concludes that while CCE has significant potential to transform assessment practices, its success depends on systemic reforms, continuous professional development of teachers, and context-specific adaptations to ensure meaningful and effective implementation in schools.